Pengkajian Penerapan Teknologi Pengolahan Manisan Mangga Kering di Kabupaten Indramayu - Wayan Sudana; Kasdi Subagyono (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2012)
Assessment on Determinant Factors of Innovation Adoption for Integrated Crop management on Rice through Integrated Crop Management-Farmer School. In order to increase national rice production, the government through the Ministry of Agriculture launched a policy of accelerated ICM in rice production centers.To support these policies, this study aims to find the determinants factors of ICM adoption by farmers, as well as the characteristics of the farmers. The data was collected through direct interviews to farmers implementing ICM in eight regions of AIAT executing of ICM-FS, with the number of respondents in each region were 10 rice farmers implementing ICM and 10 non-executing ICM farmers, hence the number of respondents were 80 ricefarmers implementing ICM and 80 non-executing ICM farmers. The results of the analysis indicated that the acceleration of innovation adoption were determined ICM by farmers include age, education level of farmers, farm costs as well as the ratio of extension worker number to researcher number in AIAT. Its means that the opportunities of ICM adoption were higher when the farmers are relatively young and the level of educations were high. The ICM-FS method of could increased the productivity up to 17% or by 0,7 t/ha compared to the existing conditions.Key Words: rice, adoption, and productivity, ICM FS Dalam rangka peningkatan produksi padi nasional, pemerintah melalui Kementerian Pertanian cepatan penerapan inovasi PTT padi terutama pada sentra produksi padi. Untuk mendukung kebijakan tersebut, kajian ini bertujuan untuk mengetahui faktor penentu adopsi inovasi PTT padi, dan hubungannya dengan karakteristik petani adopter. Pengumpulan data dilakukan melalui wawancara terhadap petani peserta PTT padi di delapan wilayah BPTP peserta SL-PTT, dengan jumlah responden per wilayah  adalah 10 petani peserta PTT padi dan 10 petani non peserta PTT padi, sehingga total responden 80 petani peserta PTT dan 80 petani non peserta PTT. Hasil analisis menunjukan bahwa ; faktor penentu percepatan adopsi inovasi PTT padi di antaranya adalah umur, tingkat pendidikan petani, biaya usahatani serta jumlah penyuluh dan peneliti di BPTP. Artinya peluang adopsi teknologi PTT makin tinggi apabila kelompok pelaksana SL adalah yangumurnya relatif muda dengan tingkat pendidikan relatif lebih tinggi dari rata-rata pendidikan anggota kelompok taninya. Metoda SL dapat meningkatkan produktivitas 17% atau 0,7 t/ha dari produktivitas yang dicapai petani selama ini.Kata Kunci : padi, adopsi, produktivitas, SL-PTT